A study on neonatal hyperbilirubinemia due to ABO incompatibility in sick newborn care unit, Telangana - Gopu, Snehalatha; Begum, Ayesha (Indian Journal of Child Health, 2018)
Background: Hyperbilirubinemia is one of the most common clinical signs encountered in neonates which if untreated is potentially neurotoxic. The neonates at higher risk of jaundice should be identified at birth and kept under enhanced surveillance for occurrence and progression of jaundice and promptly intervened. Aim: This study aims to study and analyze the neonatal hyperbilirubinemia in the babies born to O positive mother. Subjects and Methods: A prospective observational cohort study of healthy term neonates born to O positive mothers with clinical jaundice was conducted in a sick newborn care unit (SNCU) attached to a tertiary level government maternity hospital. SPSS version 19 was used for statistical analysis. Descriptive statistics such as mean, median, standard deviation, and Chi-square test were calculated. p